Vehicle maintenance and mileage tracker app - Leong, Chen Long (2024)
Nowadays, it is affordable for most families to own their automobile to reach or fetch their family members to their destination. Therefore, the quantity of vehicles is increasing along the time, resulting in a skyrocketing demand for maintenance services for the vehicles, which has become a necessity. During the celebration of the festival, a huge quantity of additional services was demanded that the service center could not handle at once. Furthermore, all vehicles that are bought will come with a user manual that includes suggestions for maintenance schedules from the manufacturer. But norms such as the owner regularly forgetting their maintenance appointment or even ignoring the maintenance might probably place themselves at risk of accidents. It is especially difficult for women to remember the scheduled tasks, such as oil changes and brake repairs, as there is a lot of stuff going on in life. Hence, it is great to have a comprehensive vehicle management tool for tracking vehicle data for multiple vehicles that could help the users keep track of all historical vehicle maintenance. This project's expected outcome is intended to help with vehicle maintenance and information tracking by providing regular maintenance and containing a vehicle logbook to keep track of all historical vehicle maintenance. The vehicle owner needs a software application to remind them of the service schedule so that they won’t miss the appointment of services and increase the safety of their vehicle and efficiency in dealing with maintenance.